2017
DOI: 10.1124/jpet.116.237701
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and Divergent Actions of Structurally Distinct Histone Deacetylase Inhibitors in Cardiac Fibroblasts

Abstract: Inhibitors of zinc-dependent histone deacetylases (HDACs) profoundly affect cellular function by altering gene expression via changes in nucleosomal histone tail acetylation. Historically, investigators have employed pan-HDAC inhibitors, such as the hydroxamate trichostatin A (TSA), which simultaneously targets members of each of the three zinc-dependent HDAC classes (classes I, II, and IV). More recently, class- and isoform-selective HDAC inhibitors have been developed, providing invaluable chemical biology p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
(71 reference statements)
2
20
0
Order By: Relevance
“…Whether HDAC inhibitors trigger senescence of cardiac fibroblasts has not been determined. However, we recently demonstrated that MGCD0103 and MS-275, but not structurally distinct HDAC inhibitors, potently stimulate expression of the SASP components PAI-1 and MMP-13 in cardiac fibroblasts (100) . Further studies are required to determine whether these Class I HDAC inhibitors are bona fide inducers of cardiac fibroblast replicative senescence, and whether other epigenetic regulators, such as BET proteins, KMTs, and DNMTs, influence the cardiac SASP.…”
Section: Epigenetics In Fibroblast Activationmentioning
confidence: 97%
See 2 more Smart Citations
“…Whether HDAC inhibitors trigger senescence of cardiac fibroblasts has not been determined. However, we recently demonstrated that MGCD0103 and MS-275, but not structurally distinct HDAC inhibitors, potently stimulate expression of the SASP components PAI-1 and MMP-13 in cardiac fibroblasts (100) . Further studies are required to determine whether these Class I HDAC inhibitors are bona fide inducers of cardiac fibroblast replicative senescence, and whether other epigenetic regulators, such as BET proteins, KMTs, and DNMTs, influence the cardiac SASP.…”
Section: Epigenetics In Fibroblast Activationmentioning
confidence: 97%
“…In mouse models of pressure overload, MI, and isoproterenol-induced cardiac injury, fibroblast proliferation spiked within the first week following induction of cardiac remodeling, and thereafter, it returned to basal levels in a manner that correlated with reduced inflammation (97) . Class I HDAC inhibitors such as mocetinostat (MGCD0103) have been demonstrated to potently suppress cardiac fibroblast proliferation and mitigate fibrotic remodeling in response to cardiac injury 98 , 99 , 100 , 101 . Thus, HDAC inhibitor–mediated suppression of cardiac fibrosis is likely due, at least in part, to the ability of these compounds to squelch expansion of the ECM-producing fibroblast pool in the heart.…”
Section: Epigenetics In Fibroblast Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, HDACs remove the acetyl groups from acetylated histones, increase chromatin condensation, and suppress gene transcription [14]. Aberrant expressions of HDACs and subsequent epigenetic modifications have been extensively observed in various animal models of interstitial fibrosis, and inhibitory effects against tissue fibrosis by HDACs inhibitors have also been demonstrated in multiple organs, such as heart [15,16], liver [17,18], and kidney [19,20], which presents the possibility of using HDACs as targets in the treatment of chronic fibrotic diseases. In this minireview, we will discuss HDACs inhibitors' application and molecular mechanism in renal interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HDAC inhibitor treatment of cardiomyocytes leads to increased expression of the anti-hypertrophic transcription factor, krüppel-like factor 4 (KLF4) [18] and increased expression of an anti-hypertrophic microRNA (miR-9) [19], with subsequent blunting of cardiomyocyte growth. In cardiac fibroblasts, HDAC inhibitors trigger cyclin-dependent kinase inhibitor gene expression, which limits expansion of fibrogenic myofibroblasts [14,20], and they stimulate expression of miR-133, which suppresses pro-fibrotic gene expression [21]. …”
Section: Introductionmentioning
confidence: 99%